Analisis Perubahan Tutupan Lahan Kecamatan Batang Anai Kabupaten Padang Pariaman Tahun 2002-2022 - Fauzan, Healdy; Syarief, Azhari (Al-DYAS, 2024)
Land cover change is a process of change from previous land cover to other land cover and is also long or temporary in nature which is a form of logical consequence of growth and transformation. The purpose of this study was to identify and determine land cover in Batang Anai Sub-district. The research method uses the overlay method, map analysis approach and also regression statistics, namely Landsat images of land cover of the study area in 2002 and 2022 sourced from the Research Center. Significant changes in the area of each category reflect major shifts in the land use structure of the area over the period 2002 to 2022. An increase in urban and wet-rice farming, along with a decrease in the area of shrubs, are highlighted. The driving factor for land change in the Batang Anai sub-district is caused by people who want to increase their income from existing land by expanding their plantation or agricultural land and also building built-up land.